Incidence and Malignancy Rates in Thyroid Nodules in North-East Indian Population by Bethesda System: A Single Institutional Experience of 3 Years - Chakraborty, Suvamoy; Balakrishnan, Manu C.; Raphael, Vandana; Tamuli, Prachurya; Deka, Anuradha (South Asian Journal of Cancer, 2022)
Introduction Goiter is one of the most common conditions encountered clinically (up to 60% of population) with thyroid malignancy being one of the most common endocrine malignancies. The American Thyroid Association has advocated the need for validation of the Bethesda system of fine needle aspiration cytology (FNAC) in each center. The risk of malignancy (ROM) for Bethesda categories in the Indian population is limited.Objective As there are variations in the effectiveness of FNAC, this study aims to study the role of FNAC in evaluating thyroid nodules, estimating the risk of malignancy in thyroid nodules in the North-East Indian population, and correlating the FNAC findings with HPE (histopathological examination).Materials and Methods A total of 110 patients with thyroid nodules had visited the Department of Otorhinolaryngology during 2017–2020. Case records were retrieved, out of which only 66 patients had both FNAC and HPE reports. The FNAC of 66 patients were studied.Statistical Analysis Data were analyzed using STATA V14. Fischer's exact test was used to determine the association of Bethesda system in diagnosing thyroid malignancy. The percentage agreement between the FNAC and HPE was calculated using the Kappa statistics. The diagnostic validity of FNAC in the diagnosis of malignant thyroid nodule was reported.Results The sensitivity, specificity, PPV, and NPV of FNAC in diagnosing thyroid malignancy were 52%, 94.3%, 89%, and 69% respectively. The risk of malignancy (ROM) for Bethesda I to VI categories in our study was 20%, 25%, 67%, 40%, 78%, and 100% respectively (p-value < 0.001, Fischer's exact test).Conclusion A specificity of 94.3% and PPV of 89% of FNAC makes it a good reliable tool in ruling in malignancy in our population. The higher ROM in indeterminate categories necessitates the need to consider thyroidectomy with or without intraoperative frozen section analysis in our population. Similar higher ROM has been reported in a few other Indian studies. These findings may suggest an increased ROM for Bethesda categories III and IV in the Indian population; however, the statement needs further validation from large multicentric studies with research to find the reason for the increased risk.
Keywords: biopsy; cytodiagnosis; fine needle; goiter; thyroid neoplasms; thyroid nodule